2021
DOI: 10.21203/rs.3.rs-429405/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gut Microbiota Alteration Influences Colorectal Cancer Metastasis to the Liver By Remodeling the Liver Immune Microenvironment

Abstract: Background: The gut microbiota regulates the liver immune microenvironment in colorectal cancer (CRC) through gut-liver axis. Kupffer cells (KCs) contribute significantly to the formation of pre-metastatic niches (PMNs) for CRC liver metastasis. The aim of our study was to explore the effect of gut microbiota regulating KCs in CRC liver metastasis. Results: Mice treated with different antibiotics were divided into Control group, vancomycin (Vanc) group, colistin (Coli) group, and a group of ampicillin, strepto… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…However, most current studies have demonstrated that KC plays a role in promoting the occurrence of CRC liver metastasis. This contrary conclusion may be caused by different immune components being activated in different experimental systems, or the interaction of other cell populations with KC is ignored ( 86 ). LSECs line the sinusoidal vessels with characteristic holes that allow liver cells and HSCs residing in the Disse space to have complete contact with the blood ( 87 ).…”
Section: Pre-metastatic Environment In Livermentioning
confidence: 99%
“…However, most current studies have demonstrated that KC plays a role in promoting the occurrence of CRC liver metastasis. This contrary conclusion may be caused by different immune components being activated in different experimental systems, or the interaction of other cell populations with KC is ignored ( 86 ). LSECs line the sinusoidal vessels with characteristic holes that allow liver cells and HSCs residing in the Disse space to have complete contact with the blood ( 87 ).…”
Section: Pre-metastatic Environment In Livermentioning
confidence: 99%